Jean-Jacques Rousseau: a formação moral através de uma educação da razão sensitiva - Santos, Whesley Fagliari dos (2019)
The theme of this research is the education elaborated by the Swiss philosopher Jean-Jacques Rousseau (1712-1778) and presented in his Emílio or education (1757). The problem that seeks to provide a solution with this study is the preparation of the young Emilio, through the development of sensory reason, so as not to be corrupted as a participant in civil society. The general objective is to establish a concrete relation between the moral formation of the subject through an applied education in an efficient way capable of giving him conditions to be an uncorrupted citizen and the ethical, political and social conduct of this citizen. The specific objectives proposed here are: To present an analysis of the hypothetical division that Rousseau makes between the man of nature and the civilized citizen, mainly in the works Discourse on the sciences and the arts (1749) and Discourse on the origin and the foundations of the inequality among men (1755). To analyze the act of man feeding on the flesh of animals, sentient beings, under the concept of piety or compassion, so important for the understanding of the natural man, Rousseau, in the work Discourse on the origin and foundations of inequality between men (1755). To investigate the criticism made regarding the formation of the moral conscience provided by an effective and substantiated education in self-knowledge and sensory reason, so that the subject is able to live free, happy and full living with and interacting with numerous other people and having real chances of not be corrupted or corrupt. The main work of Rousseau to be studied at this stage is Emilio or education (1757). The subject studied here is justified in the personal scope, since the author of this dissertation teaches in the High School for almost ten years in the state educational network and perceives the necessity of the understanding of the education proposed by Rousseau regarding the exercise of non-corruption. In the scientific academic scope the present research is of fundamental importance because it can contribute to the deepening of the studies of one of the classic philosophers that most influenced both modern education and politics. In the social sphere this study can serve as an instrument to support changes in both the educational behavior of students, teachers and teachers as well as in the ethical and political posture of individual citizens. The methodology used here was eminently bibliographical, starting with Rousseau's works. The result obtained is the conclusion that the education proposed by Rousseau, in the negative phase, strengthening the sensory reason, establishes a necessary and permanent approximation of the young citizen, materialized in the character Emílio, to the essentially natural characteristics that will allow the non-moral corruption in the middle to the dangers and problems already so deeply rooted in society.